Construção, validade e reprodutibilidade de um Questionário de Frequência Alimentar (QFA) para escolares de 9 e 10 anos de idade residentes em Cuiabá-MT - Amorim, Ana Cássia Lira de (2020)
School students are considered to be a vulnerable group from the nutritional standpoint due to the relationship between childhood nutrition and the occurrence of nutritional deviations and non-transmittable chronic diseases. The consumption assessment in this age range is essential, with special attention to the method selection. Objective: To assess the Food Frequency Questionnaire for school students according to validity and reproducibility characteristics. Materials and methods: This is a methodological study of the test-retest type, carried out with 9-10-year-old school students, of both genders, regularly enrolled in the municipal school system of Cuiabá, Mato Grosso. The sociodemographic and food consumption variables were assessed. Data were collected at school units through interviews. The food items comprised in the questionnaire were organized into groups, according to the NOVA food classification system. The assessment of reproducibility and validity was performed through the concordance and discordance rate, weighted Kappa, Intraclass Correlation Coefficient and the Bland-Altman method. Results: The constructed questionnaire was composed by a list of 68 food items, which represent the habitual consumption of the school students, with moderate reproducibility and reasonable concordance. In relation to validity, the instrument did not reflect the average consumption for every nutrient. Conclusion: the elaborated instrument was capable of representing the food consumption habit of the school students, presents moderate reproducibility, and was not considered to be valid for the assessment of the habitual food consumption of the month prior to the interview.